Pengaruh Konsentrasi Minyak Jagung (Corn Oil) Terhadap Nilai SPF Krim Tabir Surya - Claudia P.A (Program Studi S1 Farmasi, STIKES Senior, Medan, 2019)
Sunlight generates radiation composed of infrared and visible light as well as ultraviolet light A and B. Excessive UV exposure can lead to premature skin aging and possibly skin cancer. Corn oil is rich in tocopherols (vitamin e) and polyphenols which can reduce free radicals caused by UV rays. The purpose of this study is to see the effect of corn oil addition on SPF effectiveness with the combination of oxybenzone and octyl methoxycinamate sunscreen cream. The cream preparations were made 5 formulas such as Formula 1 (cream base), Formula 2 (positive control base), Formula 3 (corn oil 1%), Formula 4 (corn oil 5%), Formula 5 (corn oil 10%), where Formula 2 to Formula 5 is added oxybenzone 2% and octyl methozycinnamat 5%. Evaluation of sunscreen cream including homogeneity test, pH measurements, determination of emulsion type, irritation test, viscosity measurement, stability observation (shape, smell, and color), and SPF valuation with Uv-Vis spectrophotometry followed by a statistical test using SPSS. The result showed a homogeneous cream, o/w emulsion type, pH 6.77-6.94, non irritating, and stable in storage for 12 weeks. The SPF result showed the higher the concentration of corn oil the higher the SPF value produced. Formula 1 SPF value is 3.82 ± 0.12, Formula 2 is 13.46 ± 0.69, Formula 3 is 17.17 ± 0.10, Formula 4 is 24.10 ± 0.38, Formula 5 is 29.00 ± 1.25. From the research results obtained by the addition of corn oil to sunscreen cream preparations with a combination of oxybenzone and octyl methoxycinnamate can increase the SPF value and have good quality.